(untitled) (Journal of the College of Basic Education, 2022)
The art of design pursues various ways to communicate its implicit messages to members of society in order to communicate with each other in products and services and for this it falls under the design going into the field of the structure that will allow the field of understanding and accommodating the requirements of the needs that the design came to meet, and the design enjoys effectiveness and a large presence because it has become an important necessity in the life The individual, and for this we find him entered into every detail of our life to cover our requirements to him, and this is why the current research came to shed light on one of the design achievements that are indispensable and are continuously circulated, which are slogans, and the two researchers decided to choose the slogan of the Ministry of Oil as a waza Active in the country data and are linked by a group of circles and each special feature, you may be searching Vsolan represent the first chapter methodology research and identified the problem of researchers following their research by asking: What is the design structure of the slogans of the Ministry of Oil and its affiliated departments? As for the second chapter, the framework consists of two subjects, and the scientific material that enriches the research was presented, as well as analyzing samples and presenting the research results in addition to recommendations and proposals, as well as the most important sources covered implicitly.